PENGARUH MOTIVASI KERJA, PERILAKU PEMIMPIN DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI KANTOR INSPEKTORAT KABUPATEN TIMOR TENGAH UTARA - Lassa, Anita; Naif, Yohanes Imanuel (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2018)
This study aims to determine the influence of job motivation, leader’s behavior, and organizational climate simultaneously and partially on the employees' performance in Inspektorat Kabupaten Timor Tengah Utara.  The method applied in this research is a survey method. Analysis method utilized is multiple linear regression analysis. Variables in this study are job motivation, leader’s behavior, organizational climate, and employees' performance. Hypothesis testing results show that job motivation, leader's behavior, and organizational climate simultaneously and partially has an effect toward the employees' performance in Inspektorat Kabupaten Timor Tengah Utara.